Strenthening opportunities of economic relations between Lithuania and Sweden within the perspective of IT startup company’s development - Tunčikienė, Živilė; Sinkevičiūtė, Gabrielė (Business, Management and Economics Engineering, 2017)
Cooperation with Sweden – one of the key priorities of Lithuania. Economic cooperation potential is promising. One of the priority areas of economic activity, in which Sweden invests in Lithuania, is information and communication. In order to develop and utilize the potential for economic cooperation in the IT field, it is relevant to structuralize IT startup business success factors and to jointly develop base for decisions, execution of which would help ensure effective, economic co-operation development based with Sweden, beginning of IT startup business and such business’s continuity. To achieve the objective, following tasks were resolved: concepts of startup business and the startup company were purified, specifics inconcept’s application in the context of the parties were defined; systematized the startup business success factors and ways of strengthening them, focusing on the factors relevant for strengthening economic ties between Lithuania and Sweden within the perspective of IT startup company’s development. Systematic method of research was applied.